Cultural Sensitivity in Geriatric Care: An Exploratory Mixed-Methods Study - Sen Yang; Minerva De Ala (Health Medicine and Therapeutics, 2026)
The global demographic shift towards an aging population underscores the critical need for effective and culturally appropriate geriatric care. Existing healthcare models frequently overlook the diverse cultural backgrounds of older adults, potentially leading to communication barriers, patient dissatisfaction, and suboptimal health outcomes. This research investigates how cultural beliefs and practices shape the experiences and preferences of older adults receiving geriatric care, and examines the implications for healthcare providers in delivering culturally sensitive services. Employing a mixed-methods approach, the study combines in-depth qualitative interviews with older adults and healthcare professionals with quantitative surveys to explore the nuances of cultural influence. Key themes investigated include traditional healing practices, family involvement in decision-making, communication styles, dietary and religious preferences, and end-of-life care considerations. The findings are expected to reveal significant variations in how cultural values impact engagement with healthcare, identify specific challenges faced by providers in offering culturally competent care, and highlight areas where current practices are insufficient. This study aims to bridge a critical gap in understanding the intersection of culture and aging in healthcare by providing actionable recommendations for enhancing cultural competence among geriatric care providers. Ultimately, this research contributes to the development of more person-centered, culturally responsive geriatric care, fostering improved patient satisfaction and health outcomes.